2021
DOI: 10.1039/d1nr04847c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salt and particle concentration on the dynamic self-assembly of detonation nanodiamonds in water

Abstract: Detonation nanodiamonds self-assemble into fractal-like structures in aqueous suspensions. Our work shows that the size and shape of these structures strongly depend on the particle concentration but not on the ionic strength of the suspension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
4
1
0
Order By: Relevance
“…The spectra for center diamond-like carbon show a clear sp 3 signal at about 292 eV, without π* peak detected. It agrees well with the K-edge of diamond obtained in relevant experiments [ 42 , 44 ], further identifying its diamond-like features. As for the carbon atoms at the diamond–graphite margin, the XAS spectra are dominated by the σ* peak, with a small shoulder peak corresponding to the excitation to π* orbital (~278 eV).…”
Section: Resultssupporting
confidence: 89%
“…The spectra for center diamond-like carbon show a clear sp 3 signal at about 292 eV, without π* peak detected. It agrees well with the K-edge of diamond obtained in relevant experiments [ 42 , 44 ], further identifying its diamond-like features. As for the carbon atoms at the diamond–graphite margin, the XAS spectra are dominated by the σ* peak, with a small shoulder peak corresponding to the excitation to π* orbital (~278 eV).…”
Section: Resultssupporting
confidence: 89%
“…It should be noted that the dispersion behavior of non-functionalized DNP colloids at a low salt concentration and particle concentration range has recently been thoroughly discussed elsewhere . Nevertheless, our results as well as the previously reported literature concur that multiple factors could deviate the DLS results from the actual particle/aggregate sizes and therefore the importance of including Cryo-TEM analysis in addition to DLS is highlighted again.…”
Section: Resultssupporting
confidence: 85%
“…However, with further concentrating NaCl in the solution, the particles enlarged, indicating the aggregation of lignin particles owing to significantly weakened particle interactions via electrostatic shielding. 45 The obtained results are in accordance with the Derjaguin−Landau−Verwey−Overbeek (DLVO) theory of colloidal stability, which predicts that an increase in the salt concentration leads to a decrease in the electrostatic repulsion between particles. 46 Therefore, these results suggested that all carboxyalkylated lignin nanoparticle samples exhibited stability in the ionic strength range of 1 to 100 mM, while LNP was stable up to the salt concentration of 10 mM owing to the low concentration of anionic functional groups on its surface.…”
Section: ■ Results and Discussionsupporting
confidence: 85%
“…Still, the D H of carboxyalkylated LNPs insignificantly changed upon concentrating the NaCl concentration to 100 mM. However, with further concentrating NaCl in the solution, the particles enlarged, indicating the aggregation of lignin particles owing to significantly weakened particle interactions via electrostatic shielding . The obtained results are in accordance with the Derjaguin–Landau–Verwey–Overbeek (DLVO) theory of colloidal stability, which predicts that an increase in the salt concentration leads to a decrease in the electrostatic repulsion between particles .…”
Section: Resultssupporting
confidence: 83%